Exchange Rate Regimes and Location - Ricci, Luca (IMF Working Papers; Working Paper ;, 1997)
This paper investigates the effects of fixed versus flexible exchange rates on firms' location choices and on countries' specialization patterns. In a two-country, two-differentiated-goods monetary model, demand, supply, and monetary (as well as exchange rate) shocks arise after wages are set and prices are optimally chosen. The paper finds that countries are more specialized under flexible than fixed rates, and that the pattern of specialization is not uniquely defined by trade models but depends also on the exchange rate regime. The adoption of fixed exchange rates endogenously increases the desirability of this currency area by reducing the shock asymmetry. These results also shed light on the effects of exchange rate variability on trade.